E LOGISTICS AND DISTRIBUTED SYSTEMS FOR SUSTAINABLE SMART SUPPLY CHAIN OPERATIONS - Amelia Hayati; Zainab Ali; Omar Ahmad (Yayasan Adra Karima Hubbi, 2026)
The rapid evolution of e-logistics and distributed systems has reshaped modern supply chain operations, offering the potential for improved efficiency and sustainability. However, the integration of these technologies within supply chains remains an underexplored area, particularly in terms of their collective impact on sustainability. This study aims to explore the role of e-logistics and distributed systems in enhancing operational efficiency while minimizing environmental impact in smart supply chains. The research employs a mixed-methods approach, combining quantitative surveys with qualitative case studies across 20 supply chain organizations in manufacturing, logistics, and retail sectors. The findings indicate that e-logistics technologies, particularly blockchain, IoT, and cloud-based systems, significantly improve operational efficiency, reduce costs, and enhance supply chain visibility. However, sustainability outcomes, such as emission reductions, showed more variability, with larger organizations achieving higher environmental benefits. The study concludes that while e-logistics and distributed systems can optimize supply chain performance, their impact on sustainability is contingent upon factors such as digital maturity, organizational integration, and resource availability. The research contributes to the understanding of how these technologies can be effectively integrated for sustainable supply chain operations and provides a framework for future implementation strategies.